2011
DOI: 10.1159/000327676
|View full text |Cite
|
Sign up to set email alerts
|

Why Doesn’t the Brain Lose Weight, When Obese People Diet?

Abstract: Objective: As has been shown recently, obesity is associated with brain volume deficits. We here used an interventional study design to investigate whether the brain shrinks after caloric restriction in obesity. To elucidate mechanisms of neuroprotection we assessed brain-pull competence, i.e. the brain’s ability to properly demand energy from the body. Methods: In 52 normal-weight and 42 obese women (before and after ≈10% weight loss) organ masses of brain, liver and kidneys (magnetic resonance imaging), fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 41 publications
0
31
0
1
Order By: Relevance
“…Thus, updating the probabilities of the competing hypothesis with the help of Krieger's data gave a huge boost to the brain-pull hypothesis. Adding further evidence from experiments using state-of-the-art technology, including magnet resonance imaging and spectroscopy (Peters et al, 2011;Kubera et al, 2013;Oltmanns et al, 2008;Goodman et al, 1984;Muhlau et al, 2007) and positron-emission-tomography (Kuzawa et al, 2014), more and more increased the likelihood of the brain-pull hypothesis being true. Now, that the conventional view advocating the null hypothesis has become increasingly unlikely, it seems promising to look at the 'obesity paradox' observations in the light of brain-pull mechanisms.…”
Section: Brain Energy 'Supply and Demand'mentioning
confidence: 99%
“…Thus, updating the probabilities of the competing hypothesis with the help of Krieger's data gave a huge boost to the brain-pull hypothesis. Adding further evidence from experiments using state-of-the-art technology, including magnet resonance imaging and spectroscopy (Peters et al, 2011;Kubera et al, 2013;Oltmanns et al, 2008;Goodman et al, 1984;Muhlau et al, 2007) and positron-emission-tomography (Kuzawa et al, 2014), more and more increased the likelihood of the brain-pull hypothesis being true. Now, that the conventional view advocating the null hypothesis has become increasingly unlikely, it seems promising to look at the 'obesity paradox' observations in the light of brain-pull mechanisms.…”
Section: Brain Energy 'Supply and Demand'mentioning
confidence: 99%
“…We have recently shown that a competent brain-pull, i.e. the brain’s ability to properly demand energy from the body, functions to preserve brain mass when obese people diet [3]. By contrast, an incompetent brain-pull will lead to build-ups in the cerebral supply chain culminating in obesity and type 2 diabetes [2].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, weight loss has not been associated with changes in brain volume. In the available study addressing this issue, only global brain volume was assessed [63], thereby rendering the possibility that weight loss may still have a regional effect on brain volume. Nevertheless, some of the cognitive deficits associated with elevated BMI (that is, memory and attention/executive functioning) may be reversed after intentional weight loss [64].…”
Section: Discussionmentioning
confidence: 99%